A statistical methodology for classifying earthquake detections and for earthquake parameter estimation in smartphone-based earthquake early warning systems - Massoda Tchoussi, Frank Yannick; Finazzi, Francesco (Frontiers in Applied Mathematics and Statistics, 2023)
Smartphone-based earthquake early warning systems (EEWSs) are emerging as a complementary solution to classic EEWSs based on expensive scientific-grade instruments. Smartphone-based systems, however, are characterized by a highly dynamic network geometry and by noisy measurements. Thus, the need to control the probability of false alarm and the probability of missed detection. This paper proposes a statistical approach to address this challenge and to jointly estimate in near real-time earthquake parameters like epicentre and depth. The approach is tested using data coming from the Earthquake Network citizen science initiative which implements a global smartphone-based EEWS.